Epithelioid schwannoma of the skin displaying unique histopathological features: a teaching case giving rise to diagnostic difficulties on a morphological examination of a resected specimen, with a brief literature review. Issue 1 (December 2017) - Yamada, Sohsuke; Kirishima, Mari; Hiraki, Tsubasa; Higashi, Michiyo; Hatanaka, Kazuhito; Tanimoto, Akihide
Abstract Background Epithelioid schwannoma as a rare variant poses a challenge to all pathologists, as this uncommon entity is extremely difficult to conclusively diagnose by morphological analyses on a resected sample alone owing to its unique histopathological features. However, few papers have described the detailed clinicopathological characteristics of epithelioid schwannoma. Case presentation A 65-year-old female presented with a history of a flat and slightly elevated firm and tan plaque accompanied by occasional tenderness, measuring 10 × 8 mm, in the right joint of her hand 1 year before resection. A gross examination of a locally resected specimen revealed an encapsulated nodular lesion, yellow-whitish in color, partly filled with blood. A microscopic examination showed that the tumor predominantly consisted of a solid proliferation of epithelioid cells having mildly enlarged and round to partially spindled nuclei and abundant vacuolated or clear cytoplasm with very few mitotic figures and modest nuclear size variation, associated with focal hyalinized, cystic and hemorrhagic degeneration. This well-demarcated tumor was surrounded by dense, hyalinized and layered fibrocollagenous stroma. Immunohistochemically, these tumor cells were diffusely positive for S-100 protein and had a very low MIB-1 labeling index, and type IV collagen was strongly reactive with reduplicated basal lamina of them. We ultimately made a diagnosis of cutaneous epithelioid schwannoma. Conclusion We should be aware that, since pathologists might misinterpret epithelioid schwannoma as other soft tissue tumors, including its malignant counterpart, a wide panel of immunohistochemical antibodies can be powerful supplementary tools for identifying a very rare entity of conventional schwannoma.